Reliability Quantitative Risk Assessment in Engineering System using Fuzzy Bow-Tie - Ouache, Rachid; Ali, A. J. Adham (INPRESSCO, 2014)
uantitative risk assessment (QRA) and reliability are important approaches in modern safety to deal with reliable decision. QRA is the best approach to estimating the initiating events and its probable consequences. However, the weakness of assessment still the main problem faces its advancement. In this study, the Bow-tie analysis based on fault tree analysis and event tree analysis are proposed to solve the problem using fuzzy sets to deal with uncertainty and imprecise of results. The risk in Petroleum Company concerned in this article, where fuzzy sets is an approach used to help analysis methods to precise the values of initiating events and outcomes. The results have gotten are motivate and more precise which help us to deal with the uncertainty of initiating events and consequences.